(untitled) (Vietnam Journal of Community Medicine, 2022)
Objective: To establish a novel multiplex PCR assay for simultaneous detection of foodborne pathogens, including Salmonella spp., Shigella spp., and Entamoeba histolytica, with high sensitivity, specificity, cost-effectiveness and time-saving. Method: Multiplex PCR, Semi-Nested PCR and melting analysis for specifically amplifying and distinguishing three highly conserved target gene regions (invA, ipaH, 18S rRNA), in order to simultaneously detect Salmonella spp., Shigella spp., Entamoeba histolytica in a single reaction tube. Specific pathogens are characterized based on the melting profiles of the PCR products collected on a realtime PCR instrument following the second round of amplification. Results: The established multiplex PCR assay is capable of simultaneously detecting Salmonella spp., Shigella spp., and Entamoeba histolytica at a limit of detection of 5.86 copies/µl, 24.4 copies/µl và 53.6 copies/µl, respectively (confidence interval of 95%), the specificity reached 100% when evaluated with multiple microbial species provided by the Department of Microbiology, 103 Military Hospital. Conclusion: The novel multiplex PCR assay for simultaneous detection of Salmonella spp., Shigella spp., Entamoeba histolytica has been successfully established.